Sedimentary cycles, ammonite diversity and palaeoenvironmental changes in the Upper Cretaceous Marambio Group, Antarctica - Olivero, Eduardo Bernardo (Cretaceous Research)
Cretaceous sedimentary rocks of the James Ross Basin offer a unique Austral record of the transition from mild mid-Turonian–early Campanian to relatively cold Maastrichtian palaeoclimatic conditions. After deposition of deep-marine Lower to Upper Cretaceous sediments and tectonic inversion of the basin, the Upper Cretaceous–Danian Marambio Group reflects the development of a shelf extended for more than 100 km into the Weddell Sea. The expansion of the shelf area was punctuated by three major transgressive–regressive cycles: the N (Santonian–early Campanian); NG (late Campanian–early Maastrichtian); and MG (early Maastrichtian–Danian) sequences. Faunal groups sensitive to changing water-mass conditions, such as ammonites and inoceramids, exhibit unusual patterns of diversity changes and/or early extinctions. In the N Sequence ammonite generic richness is minimum in the Santonian, then it increases gradually to an early Campanian maximum and decreases in the latest early Campanian. This pattern is typical for transgressive–regressive cycles, where broadening of the shelf during peak transgression controls maximum diversity. The molluscs Scaphitidae, Nostoceratidae, Inoceramidae, and most Trigoniidae disappeared from Antarctica during the early Campanian. By the early–late Campanian boundary, the last Antarctic inoceramids show a distinctive shell structure that probably reflects thermal stress. In the nearby Tierra del Fuego region, deep-marine inoceramids disappeared by the early Maastrichtian, concomitant with a marked change from anoxic–dysoxic to well-oxygenated bottom conditions. The ammonites of the NG and MG sequences are dominated by kossmaticeratids, both in generic richness (which is much lower than in the N Sequence) and specimen abundance, but their diversity pattern do not reflect the expansion of the shelf during peak transgression. Dominance of the Kossmaticeratidae, concomitant with a known Austral temperature decline in the seawater, supports the idea that kossmaticeratids were stenothermal ...